BLEFAROPLASTI TEKNIK CUTLER-BEARD PADA KARSINOMA KELENJAR SEBASEA - Vonica, Linda; Setiawan, Grando; Saerang, Josefien S. M. (JURNAL BIOMEDIK : JBM, 2015)
Abstract: Sebaceous gland carcinoma is derived from Meibomian gland, Zeis gland, or sebaceous gland of caruncula. It is frequently misdiagnosed or late diagnosed because the lesion looks like chalazion or chronic blepharoconjunctivitis. The recommended therapy is wide local excision of the nodular lesion. Reconstruction of the eyelid will be done after the tumor resection either congenital or traumatic deffects. Defect of the upper eyelid that covers more than 50% of the margin needs wider excision. We reported a 48-year-old female with a lump on the right upper eyelid since a year ago associated with wedging sensation, sometimes itchy. The tumor grew slowly and had undergone curettage for 3 times. Opthalmological examination showed an irregular-formed tumor on the right upper eyelid, 1x1,5 cm, irregular surface, discrete border, associated with hard, painless, and immobile in palpation. Excision of the tumor was followed by a blepharoplasty with a Cutler-Beard flap. The pathological examination indicated a sebaceous gland carcinoma. Conclusion: In this case, the diagnosis of sebaceous gland carcinomas was confirmed based on anamnesis, opthalmological examination, and pathology examination. Excision of the tumor was followed by a blepharoplasty with a Cutler-Beard flap because the eyelid defect exceeded 50% of its margin.Keywords: sebaceous gland, blepharoplasty, Cutler-BeardAbstrak: Karsinoma kelenjar sebasea merupakan tumor ganas berpotensi mematikan yang berasal dari kelenjar Meibom, kelenjar Zeis, atau kelenjar sebasea dari karunkula. Diagnosis klinis sering terlewat atau tertunda karena lesi menyerupai kalazion atau blefarokonjungtivitis kronis. Rekomendasi terapi meliputi eksisi lokal luas pada lesi nodular. Rekonstruksi kelopak dilakukan pada defek setelah reseksi tumor baik kongenital maupun defek traumatik. Defek kelopak atas yang mengenai margin lebih dari 50% memerlukan perluasan jaringan sekitar. Kami melaporkan seorang pasien perempuan berusia 48 tahun dengan keluhan utama benjolan pada kelopak atas mata kanan sejak 1 tahun lalu disertai rasa mengganjal dan kadang-kadang terasa gatal. Benjolan membesar secara perlahan dan tetap ada walaupun sudah dikuret sebanyak 3 kali. Pada pemeriksaan oftalmologi palpebra mata kanan terdapat benjolan bentuk tidak beraturan, permukaan tidak rata, ukuran 1x1,5 cm, berbatas tegas, konsistensi keras, tidak nyeri tekan dan tidak mobile bila digerakkan. Tumor dieksisi dan dilakukan blefaropasti teknik Cutler-Beard. Hasil pemeriksaan patologi jaringan tumor menunjukkan suatu karsinoma kelenjar sebasea. Simpulan: Pada kasus ini, diagnosis karsinoma kelenjar sebasea ditegakkan berdasarkan anamnesis, pemeriksaan oftalmologis, dan pemeriksaan patologi. Eksisi tumor pada karsinoma kelenjar sebasea diikuti dengan blefaroplasti teknik Cutler-Beard karena defek pada kelopak mata atas lebih dari 50%.Kata kunci: blefaroplasti, Cutler-Beard, karsinoma kelenjar sebasea